On one condition of weak compactness of a family of measure-valued processes - Dorogovtsev, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We present a criterion for the weak compactness of continuous measure-valued processes in terms of the weak compactness of families of certain space integrals of these processes.